Immunogenic Evaluation of Ribosomal P-Protein Antigen P0, P1, and P2 and Pentameric Protein Complex P0-(P1-P2)2 of Plasmodium falciparum in a Mouse Model - Agnieszka Szuster-Ciesielska; Leszek Wawiórka; Dawid Krokowski; Nikodem Grankowski; Łukasz Jarosz; Urszula Lisiecka; Marek Tchórzewski (Journal of Immunology Research)
Malaria remains one the most infectious and destructive protozoan diseases worldwide. Plasmodium falciparum, a protozoan parasite with a complex life cycle and high genetic variability responsible for the difficulties in vaccine development, is implicated in most malaria-related deaths. In the course of study, we prepared a set of antigens based on P-proteins from P. falciparum and determined their immunogenicity in an in vivo assay on a mouse model. The pentameric complex P0-(P1-P2)2 was prepared along with individual P1, P2, and P0 antigens. We determined the level of cellular- and humoral-type immunological response followed by development of specific immunological memory. We have shown that the number of Tc cells increased significantly after the first immunization with P2 and after the second immunization with P1 and P0-(P1-P2)2, which highly correlated with the number of Th1 cells. P0 appeared as a poor inducer of cellular response. After the third boost with P1, P2, or P0-(P1-P2)2, the initially high cellular response dropped to the control level accompanied by elevation of the number of activated Treg cells and a high level of suppressive TGF-β. Subsequently, the humoral response against the examined antigens was activated. Although the titers of specific IgG were increasing during the course of immunization for all antigens used, P2 and P0-(P1-P2)2 were found to be significantly stronger than P1 and P0. A positive correlation between the Th2 cell abundance and the level of IL-10 was observed exclusively after immunization with P0-(P1-P2)2. An in vitro exposure of spleen lymphocytes from the immunized mice especially to the P1, P2, and P0-(P1-P2)2 protein caused 2-3-fold higher cell proliferation than that in the case of lymphocytes from the nonimmunized animals, suggesting development of immune memory. Our results demonstrate for the first time that the native-like P-protein pentameric complex represents much stronger immune potential than individual P-antigens.